Incarcerated Appendix Epiploica in Inguinal Hernia Sac: Treatment with Laparoscopic TAPP Approach—Report of a Rare Case - Abdullah Yildiz (Case Reports in Surgery)
Appendix epiploica (AE) in an incarcerated inguinal hernia sac is very rare. We herein report the case of a 57-year-old man admitted to the emergency department with complaints of nausea, swelling, and pain in the left inguinal area. He was diagnosed with left incarcerated inguinal hernia and treated laparoscopically with transabdominal preperitoneal (TAPP) mesh hernioplasty. During the operation, AE, lodged in the direct hernia sac, was seen to originate from the sigmoid colon. The narrow internal inguinal ring was incised at the 2 o’clock position using a monopolar hook, and the hypertrophic AE was reduced to the abdomen and resected. The patient was discharged uneventfully on the second postoperative day.